High and low frequency transcutaneous electrical nerve stimulation in post-cesarean pain intensity - Lorenna Ellen Alves Lima; Ali Sandra de Oliveira Lima; Cinara Macedo Rocha; Gabrielly Fontenele dos Santos; Amanda Júlia Ramos Bezerra; Fuad Ahmad Hazime; Janaina Mayer de Oliveira Nunes (Universidade de São Paulo, 2014)
The current study aim was evaluate the analgesic effect of TENS modulation for high (100 Hz) and low (4 Hz) frequency in post-cesarean pain. 34 postpartum women were randomly divided into three treatment groups: 100 Hz (G100), 4 Hz (G4) and Placebo (GP) (appliance off). Pain intensity was assessed by the NRS (Numeric Rating Scale) before, immediately after application of TENS, and every 20 minutes until an hour after the eletroanalgesia session. We used the Friedman test and Mann-Whitney U test (p<0.05) for statistical analysis. The results showed significant reduction of NRS in G100 only relative to pretreatment condition (p<0.05). At intervals after treatment, the G100 had a significant reduction of pain during all intervals (p<0.05). The G4 has significantly decreased only in intervals of 40' and 60', and the GP, only in the range of 60' (p<0.05). Modulation of TENS for high pulse rate showed greater analgesic effect than the low frequency TENS in post-cesarean mothers.